Review: The Emerging Role of Neutrophil Extracellular Traps in Sepsis and Sepsis-Associated Thrombosis - Chen, Zhaoyuan; Zhang, Hao; Qu, Mengdi; Nan, Ke; Cao, Hanzhong; Cata, Juan P.; Chen, Wankun; Miao, Changhong (Frontiers in Cellular and Infection Microbiology, 2021)
Patients with sepsis commonly suffer from coagulation abnormalities and lead to the formation of thrombus. During the development of sepsis, neutrophils migrate from the circulating blood to infected tissues and mediate the formation of neutrophil extracellular traps (NETs) that kill pathogens. However, the overactivation of neutrophils can promote the formation of immune thrombosis and even cause disseminated intravascular coagulation (DIC), which damages microcirculation. The outcome of sepsis depends on early recognition and intervention, so clinical evaluation of NETs function may be a valuable biomarker for early diagnosis of sepsis. The interaction of NETs with platelets, complement, and endothelium mediates the formation of immune thrombi in sepsis. Inhibiting the formation of NETs is also considered to be one of the potential treatments for sepsis. In this review, we will discuss the key role of neutrophils and NETs in sepsis and septic thrombosis, in order to reveal new mechanisms for thrombosis treatment of sepsis.